A Rural Community Translation of a Dementia Caregiving Intervention - Leisa R Easom; Gayle Alston; Ryan Coleman (Rural Nurse Organization; Binghamton University, 2013)
Purpose: This study explored the impact of the implementation of the GA REACH (Resources Enhancing Alzheimer's Caregiver Health) a multicomponent, evidence-based, tailored intervention, in eleven rural counties in Georgia. Methods: Utilizing up to nine face-to-face (in the home) and three telephone sessions, tailored education and support was provided to 85 family caregivers over a six month period. A pre-post research design was utilized to measure the impact of the intervention. Data was collected on burden, depression, health and healthy behaviors, caregiving frustrations, social support, dementia-related behaviors, and plans for institutionalization. Paired sample T-tests were used to analyze the data. Results: From baseline to six months, caregivers reported significant (p< 0.05) decreased depression, decreased burden, improved caregiver health, and decreased behavioral problems of the care recipient. Caregivers expressed feeling empowered and more capable of addressing the needs of the care recipient. Conclusions: Findings in this study indicate that the GA REACH caregiver support program can sustain the rural caregiver and improve the care environment for the care recipient. Hope for the current overburdened health care system includes the incorporation of caregiver support programs and referral to such programs by nursing and other health care providers, especially as the need for family caregivers will increase along with the number of older adults.  Keywords: rural; translation; caregiving; dementia; aging; evidence-based